Near-infrared laser-triggered drug release in a tellurium nanosystem for simultaneous chemo-photothermal cancer therapy. (12th January 2021) - Duan, Linqi; Liu, Ting; Chen, Tianfeng
Abstract : Herein, we synthesize a shape-controllable Te nanosystem, which can control the release of DOX under weakly acidic conditions to kill tumor cells, and is more effective in combination with photothermal/chemo-therapy. Abstract : Tumor cells can be selectively killed by heat application based on the different tolerances of normal cells and tumor cells to temperature. However, the limited clinical application of photothermal therapy (PTT) is mainly due to various practical implementation difficulties, of which the most important is how to fully heat the tumor. The combination of PTT and chemotherapy can synergistically enhance cell membrane permeability and reduce the dose of chemotherapy drugs to not only effectively kill the tumor but also reduce the damage to normal tissues. It is of great significance to develop materials that can be simultaneously used for tumor PTT and chemotherapy. Therefore, in this study, a functionalized tellurium (Te) nanosystem (DOX/PEI@TeNPs) was prepared to achieve chemo-photothermal cancer combination therapy. Our research showed that the DOX/PEI@TeNP morphology was controllable, and it had good photothermal conversion efficiency and light stability. Moreover, DOX/PEI@TeNPs containing doxorubicin (DOX) showed almost no drug release in normal tissues and neutral-pH environments, while in tumor cells and tissues, it massively released DOX to kill cancer cells. The as-synthesized DOX/PEI@TeNP system can produce reactive oxygen species (ROS) under near-infrared (NIR) light irradiation and features a high photothermal conversion efficiency due to its strong NIR absorbance. Therefore, this study provides an effective strategy for the effective design of nano-drugs, which can be used for the accurate chemical–photothermal synergistic therapy of tumors.